Issues of Ensuring the Economic Security of the Individual (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article is an in-depth analysis of current issues related to ensuring the economic security of an individual. The study focuses on fundamental aspects of individual economic security, including economic sustainability, risk management and strategic planning. Here we present the results of a long-term global study, which includes both theoretical and practical aspects of ensuring economic security. The article provides useful guidance and resources for those seeking to ensure their economic security in the modern world.